Endovascular Intervention for Peripheral Artery Disease. Issue 9 (24th April 2015) - Thukkani, Arun K.; Kinlay, Scott
<x xml:space="preserve">Abstract</x> Advances in endovascular therapies during the past decade have broadened the options for treating peripheral vascular disease percutaneously. Endovascular treatment offers a lower risk alternative to open surgery in many patients with multiple comorbidities. Noninvasive physiological tests and arterial imaging precede an endovascular intervention and help localize the disease and plan the procedure. The timing and need for revascularization are broadly related to the 3 main clinical presentations of claudication, critical limb ischemia, and acute limb ischemia. Many patients with claudication can be treated by exercise and medical therapy. Endovascular procedures are considered when these fail to improve quality of life and function. In contrast, critical limb ischemia and acute limb ischemia threaten the limb and require more urgent revascularization. In general, endovascular treatments have greater long-term durability for aortoiliac disease than femoral popliteal disease. Infrapopliteal revascularization is generally reserved for critical and acute limb ischemia. Balloon angioplasty and stenting are the mainstays of endovascular therapy. New well-tested innovations include drug-eluting stents and drug-coated balloons. Adjunctive devices for crossing chronic total occlusions or debulking plaque with atherectomy are less rigorously studied and have niche roles. Patients receiving endovascular procedures need a structured surveillance plan for follow-up care. This includes intensive treatment of cardiovascular risk factors to prevent myocardial infarction and stroke, which are the main causes of death. Limb surveillance aims to identify restenosis and new disease beyond the intervened segments, both of which may jeopardize patency and lead to recurrent symptoms, functional impairment, or a threatened limb.